Modeling and trade-off analysis of a capacitive silicon Mach-Zehnder modulator for telecom applications - Dourado, Diego M. (2019)
This paper presents a capacitive modulator design and modeling using poly-si and silicon technologies. We propose a methodology involving the entire modulator design process, from the optical design, charge distribution calculation and small-signal RF analysis. Thus, in the case of silicon photonics modulators, the paper proposes means to optimize the trade-offs among several figures of merit. It is shown that high bandwidth operation (>30 GHz) can be achieved by sacrificing a little the modulation efficiency.